2014
DOI: 10.1371/journal.pone.0109476
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Infectious Disease Transmission: Perceptions of CDC Health Professionals in Shanxi Province, China

Abstract: There have been increasing concerns about the challenge of emerging and re-emerging infectious diseases due to climate change, especially in developing countries including China. Health professionals play a significant role in the battle to control and prevent infectious diseases. This study therefore aims to investigate the perceptions and attitudes of health professionals at the Centers for Disease Control and Prevention (CDC) in different levels in China, and to consider adaptation measures to deal with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Mitigating the infectious disease risks of climate change-both for vectorborne and directly transmissible zoonoses-requires a deeper understanding of how it interacts with urbanization and globalization to alter the vulnerability of human populations (Tong et al 2015). Encouragingly, a recent survey of provincial public health workers in China found that the large majority had ''accurate'' (i.e., in line with existing scientific consensus) perceptions and knowledge about climate change and its likely impacts on infectious diseases (Wei et al 2014).…”
Section: Policy Implications Of China's Zoonotic Disease Risksmentioning
confidence: 99%
“…Mitigating the infectious disease risks of climate change-both for vectorborne and directly transmissible zoonoses-requires a deeper understanding of how it interacts with urbanization and globalization to alter the vulnerability of human populations (Tong et al 2015). Encouragingly, a recent survey of provincial public health workers in China found that the large majority had ''accurate'' (i.e., in line with existing scientific consensus) perceptions and knowledge about climate change and its likely impacts on infectious diseases (Wei et al 2014).…”
Section: Policy Implications Of China's Zoonotic Disease Risksmentioning
confidence: 99%
“…Research conducted among CDC staff in a Provincial CDC about their perceptions of, and attitudes towards, climate change and infectious diseases, found that CDC health professionals had noticed a climate change-related temporal and spatial change in the transmission patterns of certain infectious diseases such as vector-borne diseases, air-borne diseases and water-borne diseases [ 61 , 62 ]. Adaptation measures and actions were also proposed, such as strengthening existing disease surveillance systems and vector monitoring; building CDC capacity in terms of infrastructure and in-house health professional training; developing and improving relevant legislation, policies and guidelines; improving coordination among various government departments; engaging the community in infectious disease research and intervention, and conducting collaborative research in infectious diseases with other institutions [ 61 , 62 ]. However, the two studies were conducted in one province only and similar studies need to be conducted to enhance understanding of the associations between climatic variables and infectious diseases, and to develop appropriate climate change adaptation measures.…”
Section: Climate Changementioning
confidence: 99%
“…Another similar study conduct in china at Center for Disease and Control department employees that support our findings as the majority of respondents assumed that due to climate change or extreme weather infectious diseases are very sensitive. Moreover, more than seventy seven percent of the respondents indicated can be growth in vector-borne, food-borne, water-borne and air-borne diseases due to global warming 13 . This study found positive associations with perception regarding health effects of climate change were seen in nurse's designation management group, education level shown that fresh graduate and young has more knowledge and strong perception (p= <0.05).…”
Section: Discussionmentioning
confidence: 99%